IMPROVING STUDENTS’ VOCABULARY THROUGH SOMATIC, AUDITORY, VISUAL, AND INTELLECTUAL APPROACH - Nabila, Zulfa; Rufinus, Albert; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This study intended to improve students’ vocabulary through Somatic, Auditory, Visual, and Intellectual (SAVI) Approach to the fourth grade students of SDIT Al-Mumtaz Pontianak in academic year 2014/2015. This study was conducted through Classroom Action Research (CAR) which consisted of three cycles. The subject of this research was the fourth grade students which consisted of 31 students. The data was collected by using observation checklist table and field notes. To measure the students’ improvement on vocabulary, the writer administered the evaluation test. The research finding showed that SAVI Approach improved students’ vocabulary. In the somatic phase the students could catch up the vocabulary that they would learn. In the auditory phase students knew how to spell and to pronounce the vocabulary. In the visual phase students knew the meaning of the vocabulary and in the intellectual phase students wrote a simple sentence with the word that they learned. Students showed their improvement in every cycle. Based on the result mention above, it is concluded that teaching vocabulary by using SAVI Approach was successfully improving students’ vocabulary. Key words: Vocabulary, SAVI Approach Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan kosa kata siswa melalui pendekatan Somatic, Auditori, Visual, dan Intelektual (SAVI) pada siswa kelas empat di SDIT Al-Mumtaz Pontianak pada tahun ajaran 2014/2015. Penelitian ini menggunakan penelitian tindakan kelas yang terdiri dari tiga siklus. Sampel dari penelitian ini adalah siswa kelas 4 yang terdiri dari 31 siswa. Data dikumpulkan menggunakan tabel daftar observasi dan catatan lapangan. Untuk menghitung peningkatan pada kosa kata, penulis membuat tes evaluasi. Penemuan penelitian menunjukkan bahwa pendekatan SAVI meningkatkan kosa kata siswa. Pada tahap somatic siswa dapat menangkap kosa kata yang akan dipelajari. Pada tahap auditori siswa mengetahui bagaimana mengeja dan mengucapkan kosa kata. Pada tahap visual siswa mengetahu arti dari kosa kata dan pada tahap intelektual siswa mampu menulis sebuah kalimat sederhana dengan kosa kata yang telah mereka pelajari. Siswa menunjukkan peningkatannya pada setiap siklus. Berdasarkan hasil yang telah disebutkan diatas, dapat disimpulkan bahwa mengajar kosa kata dengan menggunakan pendekatan SAVI telah berhasil meningkatkan kosa kata siswa. Kata kunci: Kosa kata, Pendekatan SAVI